Epidural Catheter Direction and Local Anesthetic Dose. Issue 5 (September 1993) - Tiso, Robert L.; Thomas, P. Sebastian; Macadaeg, Kevin
Abstract : Background and Objectives: The volume of epidural local anesthetic required to achieve a particular dermatomal sensory level varies significantly between patients. Studies have demonstrated random cephalad or caudad migration and direction of the epidural catheter. 1 However, no studies have investigated the relationship between catheter direction and total volume of local anesthetic. Methods: The study was approved by the Institutional Review Board for the Protection of Human Subjects. After obtaining informed consent, 28 patients (13 men, 15 women) scheduled for elective total knee or hip replacements were enrolled. The epidural catheter was inserted to a depth of 3 cm at L2-3 using a standard 18-gauge Tuohy needle with bevel directed either cephalad or caudad. After test dose, incremental volumes of 0.75% bupivacaine were injected to achieve a sensory anesthetic level of T6, and the total volume of drug was recorded. Immediately after surgery, 1 ml of omnipaque dye was injected through the catheter for x-ray determination of catheter-tip position. Statistical analysis used the Student's t -test and the Wilcoxon's rank sum test. Results: Ages varied from 47 to 79 years (mean age, 66.5 ± 8.51 years). Weight ranged from 51 to 125 kg (mean weight, 81.7 ± 14.1 kg). Height ranged from 143 to 188 cm (mean height, 164.2 ± 10.6 cm). All patients had good surgical anesthesia. Statistically significant differences ( p < .001) were seen between average volumes necessary to achieve a T6 sensory level for catheters in the caudad direction (19.2 ml, n = 9) and in the cephalad direction (13.7 ml, n = 19). No statistical correlations could be demonstrated between total dose of local anesthetic and age, sex, weight, or height. Conclusions: The authors conclude that epidural catheter direction influences the total dose of local anesthetic required to achieve a specific sensory level in epidural anesthesia.